Adoption of Zai technology for soil fertility management: Evidence from Upper East region, Ghana - Gideon Danso-Abbeam; Gilbert Dagunga; Dennis Sedem Ehiakpor (Journal of Economic Structures, 2019)
Zai is a conventional soil rehabilitation management practice where organic matter is buried in a small pit to help restore fertility and conserve water in the soil. However, adoption of this environmentally-friendly technology is low. This study makes two key contributions. First, it identifies the determinants of adoption and intensity of adoption of Zai technology for soil fertility management. Second, it performs diagnostic tests to show that Cragg's double-hurdle as compared to the Heckman and the standard Tobit regression models is the best econometric approach to identify factors influencing farmers' decision to adopt and the extent of adoption~of the Zai in the Upper East region, Ghana. Results from the Cragg's double-hurdle model revealed that different set of variables affect the probability and the intensity of adoption of Zai technology. The paper concludes that farm households should be encouraged to engage in non-farm economic activities to complement their farm income and enhance the purchase of productive farm inputs. Moreover, farm-level policies oriented towards increasing access to agricultural extension services, credit facilities, and the facilitation~of farmer groups are essential to improving the adoption of farm innovations such as the Zai technology.
Keywords: 330; Adoption; Double-hurdle model; Heckman two-stage model; Intensity of adoption; Zai technology